2015
DOI: 10.1016/j.dsr2.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in the North Atlantic Ocean: The U.S. GEOTRACES zonal and meridional sections

Abstract: a b s t r a c tMercury (Hg) in the ocean undergoes many chemical transformations, including in situ production of monomethylmercury (MMHg), the form that biomagnifies in marine food webs. Because the ocean is a primary and dynamic reservoir of Hg cycling at earth's surface and the principal source of human MMHg exposures through seafood, it is important to understand the distribution of Hg and its chemical species in marine environments. We examined total Hg, elemental Hg (Hg 0 ), MMHg, and dimethylmercury (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
143
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(180 citation statements)
references
References 68 publications
(116 reference statements)
23
143
3
Order By: Relevance
“…The enhanced demethylation in oxygen minimum waters is in contrast to the general trend of elevated [MeHg] 215 in regions of net remineralization that is widespread in ocean basins (Mason and Fitzgerald, 1993;Cossa et al, 2009;Sunderland et al;Cossa et al, 2011;Bowman et al, 2015;Bowman et al, 2016). In addition, demethylation rate constants were enhanced in unfiltered waters (0.50 % d -1 , n = 4) relative to filtered waters (0.26 % d -1 , n = 7).…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…The enhanced demethylation in oxygen minimum waters is in contrast to the general trend of elevated [MeHg] 215 in regions of net remineralization that is widespread in ocean basins (Mason and Fitzgerald, 1993;Cossa et al, 2009;Sunderland et al;Cossa et al, 2011;Bowman et al, 2015;Bowman et al, 2016). In addition, demethylation rate constants were enhanced in unfiltered waters (0.50 % d -1 , n = 4) relative to filtered waters (0.26 % d -1 , n = 7).…”
mentioning
confidence: 49%
“…Because methylated Hg (collectively 35 abbreviated as MeHg) accumulates more efficiently than inorganic Hg, (Hg(II)), transformations into MeHg ultimately controls burdens in upper trophic level biota. These methylated species, monomethylmercury (MMHg) and dimethylmercury (DMHg), can be found throughout the water column, with concentration maxima often found at depths of rapid oxygen consumption (Mason and Fitzgerald, 1993;Cossa et al, 2009;Sunderland et al;Cossa et al, 2011;Bowman et al, 2015;Bowman et al, 40 2016). At these depths, production of methylated Hg has been linked to active organic matter remineralization (Cossa et al, 2009;Sunderland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, pyrite nanoparticles oxidize slowly , so the presence of trace metals means that pyrite nanoparticles may serve not only as a source of Fe to the larger oceans (Yücel et al, 2011), but also as a source of other trace metals as demonstrated by the 2011 North Atlantic GEOTRACES cruises for total Fe (Hatta et al, 2015), particulate Fe (Ohnemus and Lam, 2015), soluble Fe(II) , and soluble Hg (Bowman et al, 2015) near the TAG vent field.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Generally, dissolved gaseous mercury (DGM) in seawater includes both Hg 0 and dimethylmercury, but little dimethylmercury (generally < 5%) can be found in the surface seawater (Bowman et al, 2015;Hammerschmidt and Bowman, 2012). DGM is only a small fraction of total Hg (THg) in seawater, but plays an important role in the oceanic Hg cycle (Fu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%